(untitled) (Horizon Multidisciplinary Scientific Journal, 2026)
The article analyzes, from a scientific and pedagogical perspective, the role of physical education in maintaining and strengthening the functional stability of the human body, as well as its importance in facilitating adaptation to changing environmental conditions. The effective organization of the physical education system is regarded as one of the key means of promoting adolescents’ physical development, health, and motor activity. In this context, the potential, role in the educational process, and functional significance of activities aimed at developing motor skills and abilities—including morning gymnastics, active games, various physical exercises, and sports activities—are examined. The study particularly emphasizes the importance of conducting pedagogical and medical observations to objectively assess adolescents’ level of physical development, as well as the systematic collection, analysis, and generalization of the data obtained. Under contemporary educational conditions, it is considered appropriate to orient the objectives and content of physical education classes toward adolescents’ physical development, the formation of healthy lifestyle habits, and the achievement of strategic educational objectives. The article also highlights that physical education and sport constitute an important component of universal human culture and have held particular significance for society and the state throughout different historical periods. In addition to protecting and strengthening health, the primary purpose of physical education is to enhance individuals’ physical fitness and functional capacities. Furthermore, physical activity is emphasized as having a positive impact on stimulating cognitive development, fostering moral and volitional qualities, promoting a positive emotional state, and developing memory and other psychological characteristics. Consequently, physical education is characterized as a comprehensive pedagogical means of supporting the physical, psychological, and social development of the individual.